Development of Anti-windup PI Control and Bumpless Control Transfer Methodology for Feedwater Control System - Tran, Thanh Cong; Jung, Jae Cheon (Annals of nuclear energy, 2019)
•The block diagram of the feedwater PI controller without anti-windup scheme is developed in MATLAB/Simulink.•The back-calculation method is applied in this block diagram, the wind-up phenomenon is avoided in the PI controller of the FWCS.•The block diagram of control transfer with bumps also evolved in MATLAB/Simulink.•The tracking mode of the feedwater PI controller is enabled, the transition between an auto and a manual phases achieves smoothly. The windup phenomenon happens when the proportional-integral (PI) algorithm output is saturated. This phenomenon results in deteriorated performance, even instability, in a control system. Additionally, because control systems such as the feedwater control system (FWCS), are dynamic, it is vital to ensure that the state of the system is correct when switching the controller between manual mode and automatic mode. Therefore, the objective of this paper is to present an anti-windup scheme, and a bumpless transfer technique for the PI controller of the FWCS. The anti-windup scheme is developed using the back-calculation method, and the bumpless control transfer methodology is illustrated using a tracking mode of the PI controller at 100% reactor power level. In order to verify these designs, four scenarios are proposed: (1) performance without using an anti-windup scheme, (2) configuration of the block for anti-windup by the back-calculation approach, (3) control transfer with bumps, (4) bumpless control transfer through the use of tracking mode. Then, these scenarios are simulated in MATLAB Simulink. Throughout this simulation, the improved speed responses are obtained when the proposed methods are applied.